2023
DOI: 10.1002/ddr.22030
|View full text |Cite
|
Sign up to set email alerts
|

Two new alkaloids from Dendrobium nobile Lindl. exhibited neuroprotective activity, and dendrobine alleviated Aβ1−42‐induced apoptosis by inhibiting CDK5 activation in PC12 cells

Abstract: Dendrobium nobile Lindl. is registered in the Chinese Pharmacopoeia as a traditional medicine. Phytochemical investigation of the ethanol extract of D. nobile Lindl. stems yielded three alkaloid compounds, including two new compounds dendroxine B (2) and denrine B (3) as well as one known compound dendrobine (1). Here, we identified the structure of these compounds using spectroscopic analyses and compared them with those described in previous studies. Compounds 1-3 were found to show protective effect against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…Previous studies had shown that dendrobine treatment brought a similar trend in Aβ 1-42 -induced PC12 cell morphology. [44] Moreover, it was noted that DHSAE-3 obviously attenuated the pathological features, and almost restored the normal cell morphology (Figure 6F vs. Figure 6A).…”
Section: Neuroprotective Activities In Oxidative-stressed Pc12 Cellsmentioning
confidence: 78%
See 1 more Smart Citation
“…Previous studies had shown that dendrobine treatment brought a similar trend in Aβ 1-42 -induced PC12 cell morphology. [44] Moreover, it was noted that DHSAE-3 obviously attenuated the pathological features, and almost restored the normal cell morphology (Figure 6F vs. Figure 6A).…”
Section: Neuroprotective Activities In Oxidative-stressed Pc12 Cellsmentioning
confidence: 78%
“…nobile alkaloids can significantly improve the viability and apoptosis rate of PC12 cell induced by Aβ 25-35 , [28] and dendrobine suppressed Aβ 1-42 -induced neurotoxicity in PC12 cells. [44] Besides, SG-168 isolated from D. nobile Lindley was identified as a neuroprotective agent in H 2 O 2 -induced PC12 cells assay. [45] Therefore, we established H 2 O 2 -treated PC12 cells screening program to discover the neuroprotection of crude/purified DHAEs, and DHAE, DHSAE-3, and DHSAE-3' were subjected to the following assay.…”
Section: Neuroprotective Activities In Oxidative-stressed Pc12 Cellsmentioning
confidence: 98%
“…Dendrobine, known for its antiaging and neuroprotective effects, inhibits dopamine-related neuronal apoptosis in PD models [ 43 ] and reduces SASP factor expression in chondrocytes, suggesting potential for osteoarthritis treatment [ 44 ]. Dendroxine protects PC12 cells from Aβ1-42-induced neurotoxicity by inhibiting CDK5 [ 45 ]. Nobilonine reduces lipopolysaccharides in rats [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cheng-Chen Zhang et al found that DEN can enhance Tyr15 phosphorylation through tight binding with CDK5. 33 The specific regulatory effect of DEN on the phosphorylation of p38 and JUN needs further research.…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy, studies certified that DEN regulated the phosphorylation of p38 and JNK in osteoclasts and lung cancer cells, , but the direct effect of DEN on p38 and JUN has not been demonstrated, which is also the weakness of our study. Cheng-Chen Zhang et al found that DEN can enhance Tyr15 phosphorylation through tight binding with CDK5 . The specific regulatory effect of DEN on the phosphorylation of p38 and JUN needs further research.…”
Section: Discussionmentioning
confidence: 99%